2023
DOI: 10.1101/2023.04.28.538776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Open-loop lab-on-a-chip technology enables remote computer science training in Latinx life sciences students

Abstract: Despite many interventions, science education remains highly inequitable throughout the world. Among all life sciences fields, Bioinformatics and Computational Biology suffer from the strongest underrepresentation of racial and gender minorities. Internet-enabled project-based learning (PBL) has the potential to reach underserved communities and increase the diversity of the scientific workforce. Here, we demonstrate the use of lab-on-a-chip (LoC) technologies to train Latinx life science undergraduate student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Internet-connected microscopy enables the incorporation of organoid modules in a tissue culture undergraduate course PBL is an effective teaching approach for complex topics in biology, including teaching students who have traditionally underperformed in STEM (Ferreira et al, 2019;Petersen, 2021;Baudin et al, 2022b;Sano et al, 2023). We have previously shown that low-cost in-incubator Internet-connected microscopes can perform longitudinal imaging of cortical organoids and allow for the systematic tracking of organoid size and morphology over time (Ly et al, 2021), making them ideal tools to perform remote PBL training in the classroom (Baudin et al, 2022b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Internet-connected microscopy enables the incorporation of organoid modules in a tissue culture undergraduate course PBL is an effective teaching approach for complex topics in biology, including teaching students who have traditionally underperformed in STEM (Ferreira et al, 2019;Petersen, 2021;Baudin et al, 2022b;Sano et al, 2023). We have previously shown that low-cost in-incubator Internet-connected microscopes can perform longitudinal imaging of cortical organoids and allow for the systematic tracking of organoid size and morphology over time (Ly et al, 2021), making them ideal tools to perform remote PBL training in the classroom (Baudin et al, 2022b).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this approach allows exceptional platform scalability, allowing dozens or hundreds of users simultaneously (Baudin et al, 2022b). In the classroom, Internet-enabled technologies have been used to drive project-based learning (PBL) approaches in a variety of settings, including the use of microscopes for remote observations of behaviors of model organisms and cell cultures (Hossain et al, 2016;Ly et al, 2021;Baudin et al, 2022b), the use of sensors to monitor environmental conditions (Tsybulsky and Sinai, 2022;Tabuenca et al, 2023), and even the use of lab-on-a-chip microfluidic devices to perform bacterial detection in water samples (Sano et al, 2023).…”
Section: Introductionmentioning
confidence: 99%